2020
DOI: 10.1002/clc.23340
|View full text |Cite
|
Sign up to set email alerts
|

Coronary atherosclerosis in middle‐aged athletes: Current insights, burning questions, and future perspectives

Abstract: Regular exercise training is considered healthy as it reduces the risk of cardiovascular events and mortality. Nevertheless, athletes are not immune to the development of cardiovascular diseases and recent studies reported a higher prevalence of coronary artery calcifications and atherosclerotic plaques in athletes compared to less active controls. These observations have raised many questions among sport scientists, sports cardiologists, amateur athletes, and the general population. For example, Are athletes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
9
0
5
Order By: Relevance
“…In addition, the plaque in atherosclerosis can also harm the arterial endothelium. Repeated injuries can cause inflammation and trigger atherosclerosis blockage [30]. As a result, atherosclerosis blockage increases the risk of heart attack and stroke [31].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the plaque in atherosclerosis can also harm the arterial endothelium. Repeated injuries can cause inflammation and trigger atherosclerosis blockage [30]. As a result, atherosclerosis blockage increases the risk of heart attack and stroke [31].…”
Section: Discussionmentioning
confidence: 99%
“…While PA and exercise are unlikely to increase the risk of coronary artery calcification (CAC) at the general population level, extreme endurance ET (such as long-term marathon running) may confer an increased risk of higher CAC in a small percentage of athletes. 85 In a cross-sectional analysis of 108 healthy marathon runners ≥50 years who had completed 5 or more marathons in the preceding 3 years, the percentage of marathon runners with a CAC score ≥≥100 Agatston units (AU) was significantly greater than age- and risk factor-matched controls (36.1% versus 21.8%, P = 0.01). 86 Another small cross-sectional study of 152 masters athletes (77% runners, median 13 lifetime marathons per athlete) with a low 10-year ASCVD risk profile found that masters athletes were more likely to have a CAC score ≥300 AU compared with age- and risk factor-matched sedentary controls (11.3% versus 0%, P = 0.009).…”
Section: Primary Prevention Of Ascvdmentioning
confidence: 98%
“…Diperkirakan diseluruh dunia, PJK pada tahun 2020 menjadi pembunuh pertama tersering yakni sebesar 36% dari seluruh kematian, angka ini dua kali lebih tinggi dari angka kematian akibat penyakit kanker (PERKI 2019). Kematian akibat CVD disebabkan oleh penyakit jantung koroner aterosklerotik (Aengevaeren & Eijsvogels, 2020).…”
Section: Pendahuluanunclassified